A nonrandomized trial of a behavioral parent training intervention for parents with children with challenging behaviors: In-person versus internet-HOT DOCS. (October 2021) - Agazzi, Heather; Hayford, Holland; Thomas, Nicholas; Ortiz, Cristina; Salinas-Miranda, Abraham
Behavioral parent training (BPT) programs are the first-line interventions for childhood disruptive behaviors. In light of the COVID-19 pandemic, adapting these programs to telehealth modalities is necessary to ensure continued services to children and families. This study evaluates the use of telehealth versus in-person modality to deliver the Helping Our Toddlers, Developing Our Children's Skills (HOT DOCS) BPT. The study design was quasi-experimental with two nonequivalent groups: in-person HOT DOCS ( n = 152) and internet-HOT DOCS ( n = 46). Participants were caregivers of children ages 2–5 exhibiting disruptive behaviors. Pre- and post-intervention outcome measures were collected for child disruptive behavior and parenting stress and post-test only for consumer satisfaction. Multiple linear and Poisson regression models were performed to assess the effect of class modality on the outcomes. Child disruptive behavior and parenting stress post-test scores for in-person and telehealth groups were not significantly different, even after adjusting for baseline characteristics. Consumer satisfaction scores were significantly more positive for the in-person group. The results of this study provide preliminary evidence for the i-HOT DOCS modality as being as effective as the in-person program. Study findings may be beneficial to practitioners utilizing telehealth interventions during the COVID-19 pandemic and onward.